EKSISTENSI LAKI-LAKI DALAM MEWUJUDKAN KESERASIAN DAN KEHARMONISAN ANTAR INSAN (Kajian Tafsir Maudhu’i) - Nuraini Nuraini (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
This research is qualitative that answers two main questions, first; what is the philosophy of qur-anic verses showing men’s overplus on women. Second; how does the Qur-an expect men to actualize balance and harmony between sexes. By in depth analysis on particular verses found that al-rijal, which is referred to gender, is qualified to measure men existence. By this measurement, not all men can be grouped to ideal category. There are particular conditions that men have to fulfill in order to reach the overplus level that is given by Allah that are responsibility not only upon family but also on salvation on the earth and hereafter